EFFECT OF METHYL SUBSTITUTION IN FLAVONES ON ITS LOCALIZATION AND INTERACTION WITH DPPC MODEL MEMBRANE: IMPLICATIONS FOR ANTI-PROLIFERATIVE ACTIVITY - Sinha, Ragini; Anantram, Aarti; Joshi, Urmila J.; Srivastava, Sudha; Govil, Girjesh (International Journal of Current Pharmaceutical Research, 2015)
Objective: Flavones are an important class of naturally occurring molecules possessing multiple pharmacological activities. The anti-proliferative activity is associated with the ability of flavones to influence membrane–dependent processes. We have investigated the localization and interaction of the synthesized flavones: 4΄–methylflavone (4MF) and 4΄–methyl–7–hydroxy flavone (4M7HF) with 1,2–dipalmitoyl–sn–glycero–3–phosphocholine (DPPC) model membrane. Methods: Diferential Scanning Calorimetry (DSC) and multi nuclear NMR were used to study the interactions with DPPC model membrane. The extent of interaction of these compounds has been compared with the parent molecules: flavone (FLV) and 7–hydroxy flavone (7HF). Results: Results of DSC and NMR indicate that FLV partitions deepest inside the hydrophobic core and 7HF is localized mostly at the lipid/water interface. 4MF and 4M7HF lying in between the hydrophilic and hydrophobic core. All four molecules assume a mixed orientation with respect to the bilayer normal as indicated by chemical shifts of the lipid protons in NMR. Interaction with the membrane follows the order FLV>4MF>4M7HF>7HF. Radical scavenging activity parallels the presence of hydroxyl groups. Although FLV interacts highest with the membrane, it does not show highest antiproliferative activity. Interaction of the compounds with protons 3, 5a and 7 of DPPC is improved by the methyl substitution on the B-ring, so is the antiproliferative activity. Conclusion: That's antiproliferative activity of the compounds is at least partially related to the interaction of these molecules with the lipid water interface region.